Glutamate is required for depression but not potentiation of long-term presynaptic function - Padamsey, Z; Tong, R; Emptage, N (eLife Sciences Publications, 2017)
Hebbian plasticity is thought to require glutamate signalling. We show this is not the case for hippocampal presynaptic long-term potentiation (LTPpre), which is expressed as an increase in transmitter release probability (Pr). We find that LTPpre can be induced by pairing pre- and postsynaptic spiking in the absence of glutamate signalling. LTPpreinduction involves a non-canonical mechanism of retrograde nitric oxide signalling, which is triggered by Ca2+ influx from L-type voltage-gated Ca2+ channels, not postsynaptic NMDA receptors (NMDARs), and does not require glutamate release. When glutamate release occurs, it decreases Pr by activating presynaptic NMDARs, and promotes presynaptic long-term depression. Net changes in Pr, therefore, depend on two opposing factors: (1) Hebbian activity, which increases Pr, and (2) glutamate release, which decreases Pr. Accordingly, release failures during Hebbian activity promote LTPpreinduction. Our findings reveal a novel framework of presynaptic plasticity that radically differs from traditional models of postsynaptic plasticity.